Overcoming the Challenges of Artificial Intelligence's Negative Impact on the Common Good: Mengatasi Tantangan Dampak Negatif Artificial Intelligence Bagi Kebaikan Hidup Bersama - E.W, Tri Nugroho; Marina, Rema; Irsasri, Irsasri (Indonesian Journal of Innovation Studies, 2026)
General Background: Artificial Intelligence (AI) has emerged as a powerful technological tool that can empower humanity while also producing deceptive and frightening consequences for shared social life. Specific Background: Recent developments in AI raise ethical concerns regarding privacy, discrimination, manipulation, and the weakening of human communication, as reflected in Pope Francis’s teachings. Knowledge Gap: While prior studies discuss ethical challenges and regulatory needs, the deeper roots of AI’s negative impacts and pathways toward the common good require further ethical-critical exploration. Aims: This literature-based research aims to examine how the challenges posed by the negative impacts of AI can be overcome for the goodness of life together. Results: The study finds that AI’s harmful consequences originate in the technocratic paradigm, the myth of unlimited progress, and the neglect of human limitations. Strategic responses include directing AI toward the common good, fostering truly human communication, developing algoretics alongside algorithms, and strengthening governance through regulation and education. Novelty: This research contributes by identifying foundational ethical roots of AI’s negative impacts and proposing an integrated framework of algoretics grounded in human dignity and shared responsibility. Implications: Ethical AI governance requires transparent, inclusive, responsible, unbiased, reliable, and secure systems supported by political commitment and education, ensuring AI serves humanity rather than undermining social justice and peace. Highlights: Negative consequences of AI are rooted in technocracy, unlimited progress myths, and ignored human limits. Ethical-critical guidance calls for algoretics to accompany algorithmic development and deployment. Regulation and education are essential pillars for directing AI toward human dignity and peace. Keywords: Artificial Intelligence, Negative Impacts,The Good of Life Together.